Social Organisation of Knowledge Production in Software Work: A Qualitative Study of Two Different Firms in Chennai, India. (July 2014) - Devaraj, P.; Ilavarasan, P. Vigneswara
Based on a qualitative study, the present article examines the social organisation of knowledge production in the software work in India. The two sample firms located in Chennai city, India representing contrasting images about nature of software work were studied: a branch of a large domestic software services company—low-end programming/Fordist production model; and an Indian subsidy of a multinational software product firm—high-end software product development/flexible production model. The social organisation of software production in the two software firms are hierarchically organised, but demonstrated differential flexibility to meet the emerging market or client demands, and exhibited autonomy at the employees' level to use craft and technological knowledge through organisational procedures and routines, mediated through the project managers. It appears that prolonged engagement with the same technologies or projects works as impediment to the learning process or new knowledge production. The self-interest of the programmers motivates to engage in new knowledge production despite being directed by the organisations. The accumulated knowledge is kept within the organisations by retaining the employees through periodic pecuniary and non-pecuniary rewards, and possibilities of career leaps through technological breakthroughs. The external agents are brought in for new knowledge acquisition either through informal learning by doing or through upgradation of technological skills through training.